The potential for plant growth-promoting bacteria to impact crop productivity in future agricultural systems is linked to understanding the principles of microbial ecology - Timmusk, Salme; Pall, Taavi; Raz, Shmuel; Fetsiukh, Anastasiia; Nevo, Eviatar (Frontiers in Microbiology, 2023)
Global climate change poses challenges to worldwide land use and we need to reconsider agricultural practices. While it is generally accepted that biodiversity can be used as a biomarker for healthy agroecosystems, we must specify what specifically composes a healthy microbiome. Therefore understanding how holobionts function in native, harsh, and wild habitats and how rhizobacteria mediate plant and ecosystem biodiversity in the systems, enables us to identify key factors for plant fitness. A systems approach to engineering microbial communities by connecting host phenotype adaptive traits would help us to understand the increased fitness of the holobionts supported by genetic diversity. Identification of genetic loci controlling the interaction of beneficial microbiomes will allow the integration of genomic design into crop breeding programs. Bacteria beneficial to plants have traditionally been conceived as “promoting and regulating plant growth”. The future perspective for agroecosystems should be that the microbiomes, via multiple cascades, define plant phenotypes and provide genetic variability for the agroecosystems.